2008
DOI: 10.1128/aac.00274-08
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Compounds That Inhibit Rev-RRE Function and Human Immunodeficiency Virus Type 1 Replication

Abstract: A cell-based screening assay was performed to identify compounds that inhibited the postintegration stage of the human immunodeficiency virus (HIV) life cycle. This assay utilized a cell line that contains the HIV gag and pol genes expressed in a Rev-dependent fashion. The cell line produces about 10 to 15 ng of p24 per milliliter of medium over a 24-h period in the form of viruslike particles. Any compound that inhibits a postintegration step in the HIV life cycle scores in this assay by decreasing particle p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 70 publications
(82 reference statements)
0
35
0
Order By: Relevance
“…Previous experiments suggested that the two compounds used in this study do not directly affect Rev-RRE binding since they do not inhibit binding in vitro (46). Nevertheless, cells treated with the compounds clearly constitute an environment that compromises Rev function.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous experiments suggested that the two compounds used in this study do not directly affect Rev-RRE binding since they do not inhibit binding in vitro (46). Nevertheless, cells treated with the compounds clearly constitute an environment that compromises Rev function.…”
Section: Discussionmentioning
confidence: 68%
“…In a previous study, we described two compounds, 3-amino-5-ethyl-4,6-dimethylthieno [2,3-b]pyridine-2-carboxamide (compound 103833) and 4-amino-6-methoxy-2-(trifluoromethyl)-3-quinolinecarbonitrile (compound 104366), which were identified from a screen of 40,000, as inhibitors of Rev-RRE function and viral replication (46). In that study, using a series of reporter assays, we showed that Rev-dependent gene expression was preferentially inhibited by the compounds in cell culture, relative to control genes that did not require Rev.…”
Section: Cells Infected With Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Beige crystals, Yield: 84%, melting point: 160-162 °C (acetic acid). IR (KBr, cm (12). Yellow crystals, Yield: 90%, melting point: 220-222 °C (dioxane).…”
Section: -(5-bromobenzofuran-2-yl)pyrido[3'2':45]thieno[32-d]pyrimentioning
confidence: 99%
“…The thieno [2,3-b]pyridine derivatives occupy special place and have attracted considerable attention because of their broad pharmacological activities, including anticancer [1][2][3][4][5][6][7][8][9], antiviral [10][11][12][13], anti-inflammatory [14][15][16][17], antimicrobial [18,19], antidiabetic [20][21][22][23], antihypertensive [24][25][26] and osteogenic [27,28] activities, in addition to treatment of CNS disorders [29][30][31]. Also, pyridine derivatives of different heterocyclic nucleus have shown potent pharmacological properties like antifungal [32,33], antitubercular [34], antibacterial [35], antimicrobial [36], insecticida [37].…”
Section: Introductionmentioning
confidence: 99%